Delegation of Doctors' Authority to Nurses in Hospitals: Legal Analysis - Vitri Rohima; M. Nasser; Redyanto Sidik; Evi Karota; Jasmen Nadeak (Indonesian Journal of Global Health Research, 2024)
According to applicable laws and regulations, the law regulates professional behavior in the relationship between doctors and nurses based on the responsibility for delegating tasks and attributive authority. This study aims to analyze juridically the delegation of authority of doctors to nurses in hospitals and juridical analysis of the delegation of authority of doctors to nurses in terms of the existing lex specialist legislation. This study uses secondary data from literature review through online searches of scientific articles using three electronic databases, namely: Google Scholar, Science Direct, and Proquest, with data related to issues of delegation and authority of doctors to nurses in Indonesia. Nurses as health workers need legal protection in carrying out their duties and obligations according to their authority which has been regulated in related laws and regulations. The legal responsibility of nurses is based on the field of law in State Administrative Law, Civil Law, and Criminal Law. Meanwhile, the nurse's attribution authority is based on nursing care and is attached to the independent function of nurses carrying out tasks based on their authority. The mandate authority in the nurse's interdependent function in teamwork and delegation authority is attached to the dependent function where the nurse's interventions are the doctor's responsibility, but the duties and responsibilities are left to nurses who have met certain requirements.